Cloning, Functional Characterization, and Catalytic Mechanism of a Bergaptol O-Methyltransferase from Peucedanum praeruptorum Dunn - Zhao, Yucheng; Wang, Nana; Zeng, Zhixiong; Xu, Sheng; Huang, Chuanlong; Wang, Wei; Liu, Tingting; Luo, Jun; Kong, Lingyi (Frontiers in Plant Science, 2016)
Coumarins are main active components of Peucedanum praeruptorum Dunn. Among them, methoxylated coumarin compound, such as bergapten, xanthotoxin and isopimpinellin, has high officinal value and plays an important role in medicinal field. However, major issues associated with the biosynthesis mechanism of coumarins remain unsolved and no corresponding enzyme has been cloned from P. praeruptorum. In this study, a local BLASTN program was conducted to find the candidate genes from P. praeruptorum transcriptome database using the nucleotide sequence of Ammi majus bergaptol O-methyltransferase (AmBMT, GenBank accession No: AY443006) as a template. As a result, a 1335 bp full-length of cDNA sequence which contains an open reading frame of 1080 bp encoding a BMT polypeptide of 359 amino acids was obtained. The recombinant protein was functionally expressed in Escherichia coli and displayed an observed activity to bergaptol. In vitro experiments show that the protein has narrow substrate specificity for bergaptol. Expression profile indicated that the cloned gene had a higher expression level in roots and can be induced by methyl jasmonate (MeJA). Subcellular localization analysis showed that the BMT protein was located in cytoplasm in planta. Homology modeling and docking based site-directed mutagenesis have been employed to investigate the amino acid residues in BMT required for substrate binding and catalysis. Conservative amino acid substitutions at residue H264 affected BMT catalysis, whereas substitutions at residues F171, M175, D226 and L312 affected substrate binding. The systemic study summarized here will enlarge our knowledge on OMTs and provide useful information in investigating the coumarins biosynthesis mechanism in P. praeruptorum.